Anthropometric, biochemical and clinical assessment of malnutrition in Malaysian patients with advanced cirrhosis. - Tai, M.S.; Goh, K.; Mohd-Taib, S.H.; Rampal, S.; Mahadeva, S. (2010)
Significant malnutrition in Malaysian patients with advanced cirrhosis is common. Alcoholic cirrhosis may have more malnutrition compared to other aetiologies of cirrhosis.